Measuring the Implementation of Youth Empowerment Solutions. Issue 4 (July 2018) - Morrel-Samuels, Susan; Rupp, Laney A.; Eisman, Andria B.; Miller, Alison L.; Stoddard, Sarah A.; Franzen, Susan P.; Hutchison, Peter; Zimmerman, Marc A.
Scholars have increasingly emphasized the importance of using evidence-based programs to promote health and prevent disease. While theoretically and empirically based programs may be effective in carefully controlled conditions, many fail to achieve desired outcomes when implemented in real-world settings. Ensuring high-quality implementation of health promotion programs is critically important as variation in implementation is closely associated with program effectiveness. The purpose of this article is to present methods used to document and assess the implementation of the Youth Empowerment Solutions (YES) program. We collected process evaluation data on 25 YES groups from 12 schools over a period of 4 years. The evaluation assessed four key aspects of delivery: fidelity, dose delivered, dose received, and program quality. We found wide variations in delivery for some measures, while others were more consistent across groups. These indicators of program delivery provided a strong basis for evaluating program implementation, taking actions to improve it, and ultimately, deepening understanding of program effectiveness. The study suggests a model for using multiple methods to collect and analyze data about aspects of program delivery to guide future implementations.